Characterization of pyrolysis oil produced from organic and plastic wastes using an auger reactor. (15th February 2023) - Hasan, M.M.; Rasul, M.G.; Jahirul, M.I.; Khan, M.M.K.
Highlights: Comparative analysis of pyrolysis oils obtained from organic and plastic wastes. Waste HDPE provided the highest yield of pyrolysis oil (61.29 %) at 525 °C. Analysis of oils using GC–MS showed the presence of 12 chemical functional groups. Organic waste-derived oils contain phenolic, aromatic, and oxygenated compounds. Waste HDPE-derived oil meets most of the criteria for being an engine fuel. Abstract: The objective of this study is to assess the suitability of pyrolysis oils produced from organic and plastic wastes for engine application. The assessment was performed by comparing the properties of the obtained pyrolysis oils with those of standard engine fuel. A fast pyrolysis process with an auger reactor was used to convert organic wastes such as beauty leaf fruit husk (BLFH), macadamia nutshell (MNS), and municipal green waste (MGW), and plastic waste such as waste high-density polythene (HDPE) into oil. Prior to pyrolysis experiments, all the wastes were characterized using a thermogravimetric and a CHNS analyser to perform proximate and ultimate analyses. The experiments were performed using varied temperatures ranging from 400 °C to 550 °C at intervals of 25 °C, a 3-minute residence time and 2-mm feedstock particle size. The maximum yield of pyrolysis oil was obtained at 475 °C for BLFH (42.75 %), at 500 °C for MNS (45.09 %) and MGW (44.72 %) and at 525 °C for HDPE (61.29 %). The chemical and physical properties of the pyrolysis oils were analysed using Fourier transform infrared spectroscopy (FTIR), Gas chromatography–mass spectrometry (GC–MS), elemental and physicochemical properties analysis. The characterisation results reveal that the pyrolysis oils obtained from BLFH, MNS and MGW are enriched with phenolic, aromatic, and oxygenated compounds and oil obtained from HDPE contains mostly hydrocarbons and aromatics. The BLFH, MNS and MGW derived oils have higher viscosity and density and lower calorific value compared to that of HDPE derived oil. Due to these features, the oils obtained from organic wastes are not suitable for engine application without further refinement. HDPE derived oil, on the other hand, meets most of the criteria to be an engine fuel. However, a firm conclusion cannot be drawn until this oil has been tested in an engine.